ANALISIS FAKTOR YANG MEMPENGARUHI PEMBIAYAAN MUSYARAKAH DI PERBANKAN SYARIAH - Nazli Aulia; Nidaul Husna; Salma Indriani; Muhammad Ikhsan Harahap (CV. Barokah Publsiher, 2025)
Musharakah financing represents a core profit-and-loss sharing (PLS) instrument in Islamic banking, designed to promote equitable risk-sharing and support productive economic activities. However, its proportion within the financing portfolio of Islamic banks in Indonesia remains relatively limited and fluctuative compared to non-PLS contracts. This study aims to analyze the factors influencing musharakah financing in Islamic banking by focusing on internal bank performance indicators and external macroeconomic conditions. This research employs a qualitative approach using a literature review method, drawing upon previous empirical studies, Islamic banking statistics, and regulatory documents related to PLS financing. The analysis reveals that internal factors such as non-performing financing (NPF), operational efficiency (BOPO), capital adequacy ratio (CAR), and third-party funds (DPK) consistently influence banks’ decisions in channeling musharakah financing. In addition, external factors including economic growth, inflation, and regulatory frameworks also play a significant role in shaping banks’ risk preferences toward partnership-based financing. These findings indicate that strengthening risk management, improving operational efficiency, and ensuring adequate capital structure are essential to support the sustainable development of musharakah financing in Islamic banking. This study is expected to contribute to the academic discourse on profit-sharing financing and provide strategic insights for Islamic banks in optimizing their financing portfolios.